Early Environmental Awareness Character Education Through Ecoenzyme-Making Training For Telkom Padang Elementary School Students - Awalina, Rahmi; Wellyalina, Wellyalina; Hafizulhaq, Fadli; Lubis, Muhammad Iqbal Abdi (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2023)
Environmental education needs to be introduced early on to students from elementary school so that it becomes a provision for every student to have a caring attitude in protecting the environment so that the earth remains sustainable. One of the efforts was carried out through ecoenzyme training for elementary school residents and training students in organic waste management to be useful again. This activity was carried out in the Telkom Padang Elementary School (SD), Padang City, West Sumatra. It consists of two stages of activity, namely counseling on organic waste management and the practice of making ecoenzyme. The implementation of these activities went well for three months from November 2022 to February 2023. The results of this activity were educating elementary school students about the importance of preserving the environment by processing waste into ecoenzymes and forming a positive character of loving the environment from an early age in students and residents school.